A classroom discourse analysis of teacher-students interaction: A case study on Sinclair and Coulthard’s model at Madrasah Tsanawiyah NU 15 Jurangagung - Baharudin Maghfur (Journal of English Language and Pedagogy, 2021)
This study analyzes the classroom interaction between teacher and students in MTs NU 15 Jurangagung using Sinclair and Coulthard’s model. This study aims at describing how the teacher initiates the exchanges, how students respond to the initiations, and how the teacher follows up the exchanges. The researcher found that the interaction was teacher-centred. It meant the teacher dominated most of the exchanges. He also found that the interaction is sufficient for the students to pass the exam, but not for them to acquire the skills. Several reasons such as most of the students were not expected to go to college, English was being the least important language they learned, and their parents who expected them to learn Arabic more play the part on why the English language skills acquisition was not effective.